A tortoise approach for US nuclear research and development. (October 2018) - Ford, Michael; Schrag, Daniel
In Aesop's fable, a swift hare races with a deliberate tortoise. In the end, the tortoise wins by taking a slow and steady approach. We argue that, given the economic constraints on US deployment of nuclear power, a 'tortoise strategy' is more prudent for US government nuclear R&D efforts.